Economic policy - Sandford, Cedric T.; Bradbury, Malcolm S. (London : Macmillan; New York : St Martins Press, 1970)
This volume is designed as a study and workbook containing case studies of detailed examination of situations, events or developments by means of which economic principles or concepts can be learnt.
Includes bibliographical references.
lje 25/01/2019
Loans
Keywords: Economic policy; Great Britain